2021
DOI: 10.1096/fj.202000007rrr
|View full text |Cite
|
Sign up to set email alerts
|

Female serotonin transporter‐knockout rat: A potential model of irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disease. Although visceral hypersensitivity (VH) and disturbed gastrointestinal motility are typical pathophysiological features of IBS, the pathological mechanisms underlying this disease remain unclear. Serotonin system abnormalities are considered to play an important role in the pathomechanisms of IBS. Here, we hypothesize that similar alterations, including VH and colonic motility, induced by serotonin transporter (SERT) knockout resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
(133 reference statements)
0
12
0
Order By: Relevance
“…Excessive release of 5-HT can cause mucosal damage and a reduction in blood flow [ 73 ]. In this case, ECs are sentinels for sensing the variations in gut mechanisms and their functions are not yet well known; Xu et al, (2021) and Bi et al, (2021) demonstrated that knockout mice for 5-HT transporters showed visceral sensitization, GI disorders and an increased the relative proportion of ECs and colon 5-HT concentration [ 43 , 74 ]. This mechanism has been explained by suggesting that the release of 5-HT from ECs is related to adenosine triphosphate; this can activate the pain network to the brain through afferent nerve fibers and enteric nerve reflex [ 74 ].…”
Section: Heterogeneity Of Enterochromaffin Cellsmentioning
confidence: 99%
“…Excessive release of 5-HT can cause mucosal damage and a reduction in blood flow [ 73 ]. In this case, ECs are sentinels for sensing the variations in gut mechanisms and their functions are not yet well known; Xu et al, (2021) and Bi et al, (2021) demonstrated that knockout mice for 5-HT transporters showed visceral sensitization, GI disorders and an increased the relative proportion of ECs and colon 5-HT concentration [ 43 , 74 ]. This mechanism has been explained by suggesting that the release of 5-HT from ECs is related to adenosine triphosphate; this can activate the pain network to the brain through afferent nerve fibers and enteric nerve reflex [ 74 ].…”
Section: Heterogeneity Of Enterochromaffin Cellsmentioning
confidence: 99%
“…T. spiralis and Campylobacter jejuni reduce SERT expression in the gut [100,101], while L. rhamnosus upregulated gene expression and protein levels of SERT in a rat model of PI-IBS [100], and Lactobacillus acidophilus and Bifidobacterium longum supernatants to upregulate SERT expression in HT-29 and Caco-2 cells [102]. SERT deficiency is related to dysbiosis and changes in the metabolic function of the mouse enteric microbiome [94], and female SERT -/rats showed visceral hypersensitivity and accelerated GI motility [118]. In humans, reduced SERT expression was observed in the rectal tissue of patients with IBS [119].…”
Section: Akkermansia Muciniphilamentioning
confidence: 99%
“…Some studies have found that IL-6, a pro-inflammatory cytokine, is significantly elevated in patients with IBS, which can regulate intestinal secretion and participate in the development of IBS ( O’Brien et al, 2021 ). Regarding the Tryptophan metabolism pathway, studies have found that the decreased serum tryptophan concentration exhibited by SERT –/– rats is associated with visceral hypersensitivity and abnormal gastrointestinal motility ( Bi et al, 2021 ). In addition, the tryptophan metabolic pathway is considered to be one of the main metabolic pathways in the WAS-induced IBS model rats, and the changes in the intestinal microbiota of the model rats are closely related to the changes in tryptophan metabolism ( Mishima and Ishihara, 2021 ).…”
Section: Discussionmentioning
confidence: 99%